Pengawasan Penegakan Kemitraan UMKM dan Pelaku Usaha Besar - Dwi Lestari, Nadila; Tri Yulia, Fadilah; Lestari, Fitrianing; Arsita, Selvira Maharani (Universitas Muhammadiyah Bima, 2025)
The partnership between Micro, Small, and Medium Enterprises (MSMEs) and large businesses represents a strategic collaboration with significant potential to drive inclusive economic growth in Indonesia. MSMEs, as drivers of local economies and key contributors to Gross Domestic Product (GDP), require support from large businesses that possess access to global markets, resources, and expertise. However, imbalances in these partnerships—particularly in resource management, decision-making, and profit-sharing—often disadvantage MSMEs, exposing them to risks such as exploitation, monopolization, and restricted innovation. To address these challenges, the government has established regulatory frameworks, including Law No. 20 of 2008 and KPPU Regulation No. 1 of 2015, to promote equitable partnerships, with oversight as a crucial mechanism to ensure compliance with principles of fairness and transparency. This study, employing a library research method, explores printed and digital literature to analyze the imbalances within such partnerships. The findings emphasize that effective oversight can safeguard MSMEs, foster mutually beneficial collaboration, and support more equitable and inclusive economic growth.